Variability in oxidative stress biomarkers following a maximal exercise test. (10th July 2013) - Mullins, Anna L.; van Rosendal, Simon P.; Briskey, David R.; Fassett, Robert G.; Wilson, Gary R.; Coombes, Jeff S.
Abstract: The oxidative stress response to maximal exercise may provide useful clinical biomarkers for assessing redox homeostasis. The aim was to determine the between-individual variability in the exercise-induced change in oxidative stress measures and investigate predictors of these responses. Plasma F2-isoprostanes (Isop), protein carbonyls (PCs), glutathione peroxidase (GPX) activity and total antioxidant capacity (TAC) were measured before and after a maximal treadmill exercise test. Exercise produced significant increases in Isop (27.0%), PC (6.2%) and GPX (7.8%). There were large between-individual coefficients of variation: Isop (152%), PC, (240%), GPX (130%) and TAC (243%).